Wood, Frank (London, 2013)
2013 "Wood, Frank", 2013, HistoryTalk Frank Wood studied for a degree in biochemistry and physiology at North East London Polytechnic in Stratford in the mid-80s. After doing voluntary work at Friends of the Earth on City Road for a year, he began work at Central Middlesex Hospital at Park Royal in west London as a trainee pathology scientist.